Teaching Vocabulary Acquisition through Derivational Suffixes of SMP Santo Petrus Medan in the Academic Year 2017/2018 - Karisma Erikson Tarigan; Margaret Stevani (BIRCU, 2020)
This study is aimed to improve the students’ vocabulary acquisition through derivational suffixes strategy. The subject of this study is the students of Class IX-1 of SMP Santo Petrus Medan in the academic year of 2017/2018. This study is conducted by applying Classroom Action Research (CAR), which have been conducted in two cycles (cycle 1 and cycle 2) and each cycle consisted of four meetings. The results of vocabulary test shows that the progressing mean score of the pretest is 34.66, post test in cycle 1 is 93.46, and post test in cycle 2 is 97.33. In cycle 1, the comparison percentage of nominal is 88.83%, verbal is 77.46%, adjectival is 40.74%, and adverbial is 84.14%. In cycle 2, the comparison percentage of nominal is 100%, verbal is 95.45%, adjectival is 65.84%, and adverbial is 94.91%. The percentage of the students who pass Minimal Criterion Mastery in each cycle is 100%, with the improvement 169.64% in cycle 1 to 180.81% in cycle 2. These indicate that there is a significant improvement of the students’ vocabulary mastery through affixation strategy of Class IX-1 of SMP Santo Petrus Medan in the academic year of 2017/2018.